THE ROLE OF SURDOPEDAGOG TEACHERS IN IMPROVING THE EFFECTIVENESS OF THE EDUCATION OF DEAF AND WEAK HEARING CHILDREN (Academicia Globe: Inderscience Research, 2024)
The role of deaf pedagogic teachers in increasing the effectiveness of the education of deaf and hard-of –hearing children, teachers competencies, correctional orientation of lessons, teachers conduct lessons, based on the principle of integrity, attend lessons and the requirements for teachers are oriented to the correction of lessons. The positive effects and results of the equipment on educational effeciency are highlighted.